Mortality after pulmonary embolism in patients with diabetes. Findings from the RIETE registry - de Miguel-Díez, Javier; López-de-Andrés, Ana; Jiménez-Trujillo, Isabel; Hernández-Barrera, Valentín; Jiménez-García, Rodrigo; Lorenzo, Alicia; Pedrajas, José M; Visonà, Adriana; López-Miguel, Patricia; Monreal, Manuel and the RIETE Investigators; Bosevski, Marijan; Zdraveska, Marija (Elsevier BV, 2019)
Among patients presenting with pulmonary embolism (PE), those with diabetes are at increased risk to die than those without diabetes. The reasons have not been identified. We used the RIETE (Registro Informatizado Enfermedad Trombo Embólica) database to compare the mortality rate and the causes of death during anticoagulation in patients with PE according to the presence or absence of diabetes.